The Influence of Corporate Social Responsibility, Fiscal Loss Compensation, and Executive Risk Preference on Tax Avoidance - Lindawati, Lindawati; Putri, Wulandari Cahyani; Muarif, Syamsul (Sean Institute, 2025)
Tax avoidance remains a critical issue for governments and businesses, as it directly impacts state revenue, corporate reputation, and public trust. In Indonesia’s food and beverage industry, the complexity of regulations and diverse corporate strategies create opportunities for tax avoidance that warrant closer examination. This study analyzes the influence of corporate social responsibility, fiscal loss compensation, and executive risk preference on tax avoidance among food and beverage companies listed on the Indonesia Stock Exchange during 2018–2022. Using a quantitative approach, the research employs secondary data from annual financial reports and applies panel data regression analysis. The results show that, simultaneously, all three variables significantly affect tax avoidance. However, partially, corporate social responsibility and fiscal loss compensation have no significant effect, while executive risk preference has a significant negative impact, indicating that risk-averse executives are less inclined to adopt aggressive tax strategies. These findings provide empirical evidence on behavioral and institutional factors shaping corporate tax behavior and highlight the role of executive characteristics in tax policy. The study is limited by its sector-specific sample and selected variables, suggesting opportunities for broader research in the future.